Factors Shaping Physicians? Adoption of Telemedicine: A Systematic Review, Proposed Framework, and Future Research Agenda - Al-Emran M.; Al-Qaysi N.; Al-Sharafi M.A.; Alhadawi H.S.; Ansari H.; Arpaci I.; Ali N. (Taylor and Francis Ltd., 2025)
Telemedicine offers transformative solutions for healthcare delivery, particularly in bridging geographical barriers and enhancing patient care. Nevertheless, its adoption by physicians is intricate, driven by diverse factors that require systematic understanding. This systematic review aims to identify and classify the factors influencing physicians? adoption of telemedicine. From a collection of 2098 articles sourced from Web of Science and Scopus databases, 59 studies met the predetermined criteria and were meticulously assessed. The salient factors from these chosen papers were segmented into distinct categories: psychological and behavioral factors, technological factors, social and cultural factors, security and privacy factors, conditional factors, quality factors, healthcare-related factors, and inhibiting factors. Building on this classification, we proposed a comprehensive framework for telemedicine adoption tailored to physicians. This framework endeavors to act as a scaffold for subsequent empirical investigations. The taxonomy of the factors also aided in offering numerous research agendas to pave the way for more exhaustive studies into telemedicine adoption among medical professionals. The insights procured serve not only to deepen theoretical comprehension but also to present pragmatic guidelines for practitioners, service providers, application developers, and decision-makers. ? 2024 Taylor & Francis Group, LLC.